Growth and Yield Responses of Red Chili to Various Foliar Fertilizers - Puji Harsono; Moch. Irfan Khakim; Gani Cahyo Handoyo; Supriyono Supriyono (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2025)
Red chili production in certain areas of Central Java, including Sendangijo Village, Wonogiri Regency, remains relatively low. One alternative to improve its growth and yield is foliar fertilization. This study aimed to determine the most effective type of foliar fertilizer for enhancing the growth and yield of red chili. The study was conducted from May to September 2023 in Sendangijo Village using a Randomized Complete Block Design with a single factor consisting of four treatments: no foliar fertilizer, foliar fertilizer A. NPK 11-8-6, B. NPK 20-15-15, and C. NPK 10-2-7, each with six replications. Observed variables included plant height, number of dichotomous branches, number of leaves, leaf area, fresh and dry weight of biomass, number of fruits, fresh weight of fruits per plant, and productivity per hectare. The result showed that the leaf area of red chili pepper given foliar fertilizer NPK 20-15-15 was larger than the foliar fertilizer NPK 11-8-6, NPK 10-2-7, and without foliar fertilizer. Foliar fertilizer NPK 20-15-15 also gave a heavier dry weight of biomass compared to foliar fertilizer NPK 11-8-6, NPK 10-2-7, and without foliar fertilizer. However, foliar fertilizer application did not significantly affect the number of fruits, the fresh weight of fruits per plant, or productivity per hectare.